The Mysterious Green Streaks Below STEVE. Issue 4 (9th November 2020) - Semeter, Joshua; Hunnekuhl, Michael; MacDonald, Elizabeth; Hirsch, Michael; Zeller, Neil; Chernenkoff, Alexei; Wang, Jun
Abstract : Strong thermal emission velocity enhancement (STEVE) is an optical phenomenon of the subauroral ionosphere arising from extreme ion drift speeds. STEVE consists of two distinct components in true‐color imagery: a mauve or whitish arc extended in the magnetic east–west direction and a region of green emission adjacent to the arc, often structured into quasiperiodic columns aligned with the geomagnetic field (the "picket fence"). This work employs high‐resolution imagery by citizen scientists in a critical examination of fine‐scale features within the green emission region. Of particular interest are narrow "streaks" of emission forming underneath field‐aligned picket fence elements in the 100‐ to 110‐km altitude range. The streaks propagate in curved trajectories with dominant direction toward STEVE from the poleward side. The elongation is along the direction of motion, suggesting a drifting point‐like excitation source, with the apparent elongation due to a combination of motion blur and radiative lifetime effects. The cross‐sectional dimension is <1 km, and the cases observed have a duration of ∼20–30 s. The uniform coloration of all STEVE green features in these events suggests a common optical spectrum dominated by the oxygen 557.7‐nm emission line. The source is most likely direct excitation of ambient oxygen by superthermal electrons generated by ionospheric turbulence induced by the extreme electric fields driving STEVE. Some conjectures about causal connections with overlying field‐aligned structures are presented, based on coupling of thermal and gradient‐drift instabilities, with analogues to similar dynamics observed from chemical release and ionospheric heating experiments. Plain Language Summary: STEVE is a recently identified atmospheric phenomenon caused by supersonic plasma jets flowing at altitudes >100 km. STEVE appears as a whitish pink arc extending in the magnetic east–west direction, which is often accompanied by an adjacent region of green features. In some cases, the green features appear as periodic vertical columns resembling a "picket fence". These features were thought to be caused by the same mechanism as the aurora, but the color is wrong. This article examines these features from a morphological perspective. We use time lapse images recorded by citizen scientists to examine fine‐scale structures in STEVE's green emission region. We focus particular attention on a narrow streak of emission commonly observed underneath the picket fence. These streaks have width of just a few hundred meters and propagate horizontally. They have identical coloration to other green objects in the field, suggesting a common source. Although we cannot state conclusively what that source mechanism is, they are most likely excited by turbulent heating related to the extreme plasma flows of STEVE. Our initial analysis suggests a physical connection between these tiny streaks and the extended picket fence features above them. Advancing this physics will benefit greatly from continued involvement of citizen scientists. Key Points: Extremely small point‐like features are observed within the "picket fence" STEVE phenomenon Such features point to the role of local ionospheric production The features are among the smallest optical features found in the natural airglow or aurora